2005
DOI: 10.1021/jf050338i
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Ethanolic Extracts from Several Asparagus Cultivars

Abstract: Three different methods (antiradical activity, inhibition of primary oxidation, and ferric reducing power) have been used to evaluate the antioxidant activity of eight different asparagus cultivars and byproducts: white and green asparagus from Alcalá del Río (Guadalquivir Valley, Seville) and American hybrids, native spears, and their byproducts from Huétor-Tájar (Vega de Granada). The correlation between antioxidant activity and total phenol content was studied. Six standards were also tested to validate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 30 publications
7
71
0
1
Order By: Relevance
“…It has been shown that, compared to other onions, it reduces their content in flavonoids, a group of polyphenolic compounds with antioxidant activity (Santas et al, 2008), probably in a similar way to what occurs to white asparagus (Rodriguez et al, 2005). According to their differential flavour, pungency and odour -characteristics known to be associated with organosulphur compounds (Jones et al, 2004;Lanzotti, 2006) -"calcots" also probably contain lower, but still significant, levels of these toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that, compared to other onions, it reduces their content in flavonoids, a group of polyphenolic compounds with antioxidant activity (Santas et al, 2008), probably in a similar way to what occurs to white asparagus (Rodriguez et al, 2005). According to their differential flavour, pungency and odour -characteristics known to be associated with organosulphur compounds (Jones et al, 2004;Lanzotti, 2006) -"calcots" also probably contain lower, but still significant, levels of these toxins.…”
Section: Discussionmentioning
confidence: 99%
“…It is planted, replanted and successively covered in soil in order to prevent photosynthesis, so that the edible part remains white. The process is similar to the production of white asparagus (Asparagus officinalis), another liliaceae, a fact that explains the differences between the organoleptic and chemical composition of the white and green types of this vegetable (Rodriguez et al, 2005). The "calcot" is collected young, before the plant fully develops, and is 15-25 cm long and 1.7-2.5 cm diameter in the edible stem (onion bulb not yet present), which makes its shape similar to a green onion, but with a distinctive colour and flavour.…”
mentioning
confidence: 84%
“…The effi ciency of the extraction processes is dependent on the properties of the compounds extracted, or their solubility in the solvent used (Rodríguez et al, 2005;Suhaj, 2006). According to the general principle .…”
Section: Resultsmentioning
confidence: 99%
“…As the odd electron of the radical becomes paired off in the presence of a hydrogen donor that is a free radical scavenging antioxidant the absorption strength decreases and the resulting decolorization is stiochiometric with respect to the number of electrons captured 26 . This reaction has been widely used to test the ability of compounds to act as free radical scavengers or hydrogen donors and to evaluate the anti-oxidative activity of foods and plant extracts [27][28][29][30] . The extract showed to possess DPPH radical scavenging ability as compared to the standard.…”
Section: Discussionmentioning
confidence: 99%